Study on Mechanical Problems of Complex Rock Mass by Composite Material Micromechanics Methods: A Literature Review - He, Junzhao; Li, Yunan; Jin, Yuling; Wang, Anming; Zhang, Yumin; Jia, Jinchao; Song, Hei; Liang, Dong (Frontiers in Earth Science, 2022)
The mechanical analysis of complex rock mass is a difficult problem, which often occurs in scientific research and practical engineering. Many achievements have been made in the study of rock mass composite problems by using composite micromechanics method, but it has not been well summarized so far. This paper summarizes in detail the research status of complex rock mass problems by using composite material micromechanics method at home and abroad, including the application of Eshelby equivalent inclusion theory and self consistent model in rock mass composite problems, and the application of homogenization method in jointed rock mass and other rock mass composite problems such as anchored rock mass, layered rock mass and salt rock mass with impurities. It is proposed that the structural similarity and mechanical analysis similarity should be satisfied when the composite material micromechanics method is used to study the complex rock mass. Finally, the problems that need to be further studied are put forward. The research results provide a valuable reference for the study of complex rock mass by composite material micromechanics method.